Gender Inequality: Concept and Measurement (A Study of Indonesia on ASEAN) - Bangun, Wilson (International Journal of Engineering and Technology, 2018)
Indonesia is the largest country in ASEAN but has the largest gender gap in ASEAN-5. This study aims to know the large of gender inequality in Indonesia on ASEAN. Five important dimensions to measurement of gender inequality, there are economic participation, economic opportunity, political empowerment, educational attainment, and health and well-being. This research is an empirical study using secondary data from various sources are relevant. For measurement gender inequality is used the calculating of Gender Inequality Index. The assessment is done on Indonesia and other countries in Southeast Asia. The research results showed that Indonesian Gender Inequality is largest in ASEAN-4, instead higher than Viet Nam. It means the gender equality in Indonesia is lowest more than Singapore, Malaysia, and Thailand in human development. Indonesian had to improving the role of woman in participation of education, economic, political, and public job reproductive health, empowerment, and labour market. The most striking indicator is the low representation of women in parliament. It is seen that almost all ASEAN member countries have low representation of women in parliament. The majority of Indonesian workers are unskilled labor. Similarly, the woman far slightly in the labor force to compared with man.